Multiscale Modeling of SiCf/SiC Nuclear Fuel Cladding Based on FE-Simulation of Braiding Process - Feng, Yajie; Wang, Jun; Shang, Nianwei; Zhao, Gang; Zhang, Chao; Tang, Jianbo; Xin, Shiqing; Hornig, Andreas; Gude, Maik; Huang, Qing; Jian, Xigao; Xu, Jian (Frontiers in Materials, 2021)
A generalized multiscale (micro-macro) finite element (FE) model for SiC-fiber reinforced SiC-matrix ceramic (SiCf/SiC) nuclear fuel claddings is established. In the macro-level, the solid mesh of braided preform, which can be tailored by machine settings (braid angle, yarn width, cover factor), is generated based on the braiding process simulation using the dynamic FE-solver, hiring the contact constrains. The matrix mesh and the yarn mesh are integrated by the embedded region constrain, with which the meshing difficulties can be avoided. In the micro-UD model, the progressive damage of the ceramic matrix is modelled using the phase field method (PFM) and the fracture is captured by Mohr-Coulombs criterion, which are stable and efficient in the description of the brittle crack initiation, coalition, and branching. Based on this multiscale model, the mechanical behaviour of the braided SiCf/SiC nuclear fuel cladding tube is detailed studied. The superiorities over the homogenised tube model are demonstrated, too.